Tomato aspermy virus elimination improves medicinal quality of chrysanthemum - Zhao, Xiting; Jiang, Liwei; Liu, Ke; Ma, Megndan; Zhou, Yingyuan; Tian, Ying; Li, Mingjun (Archives of Biological Sciences, 2018)
Paper description: Chrysanthemum morifolium cv. ‘Huaihuang’ is a well-known medicinal plant in China, but virus infections greatly reduce its medicinal quality. Many studies have shown that detoxification can help crops grow better, however, the effect of detoxification on crop quality has received little scientific attention. Tomato aspermy virus (TAV) is the main virus disease of ‘Huaihuang’. In this study, we verified that TAV elimination can greatly improve the medicinal quality of ‘Huaihuang’. This work provides the evidence that eliminating TAV is an effective way to improve the medicinal quality of chrysanthemum. Abstract: Chrysanthemum morifolium cv. ‘Huaihuang’, a medicinal chrysanthemum of China, undergoes long-term asexual reproduction and virus infection that change its quality characteristics. Our previous studies have shown that tomato aspermy virus (TAV) is the main virus infecting ‘Huaihuang’. Many studies indicate that plant virus elimination can improve plant growth, but only a few studies have focused on the effects of detoxification on the medicinal components of medicinal plants. In this paper, the content of medicinal components, including chlorogenic acid, luteoloside and 3,5-O-dicaffeoylquinic acid, was compared between the TAV-free and TAV-infected (control) chrysanthemum. In addition, the reason why TAV elimination improves the medicinal components of chrysanthemum is explored. Our results suggest that TAV elimination significantly improves plant growth, enhances the enzyme activities of phenylalanine ammonia-lyase, cinnamate-4-hydroxylase and 4-coumarate:CoA ligase, and increases the levels of CmHCT and CmCHS expression, thereby greatly improving the medicinal quality of chrysanthemum. https://doi.org/10.2298/ABS171226010Z Received: December 26, 2017; Revised: February 19, 2018; Accepted: March 15, 2018; Published online: March 22, 2018 How to cite this article: Zhao X, Jiang L, Liu K, Ma M, Zhou Y, Tian Y, Li M. Tomato aspermy virus elimination improves medicinal quality of chrysanthemum. Arch Biol Sci. 2018;70(3):…